A tripartite game model of trust cooperation in cloud service. Issue 106 (July 2021) - Sun, Pan Jun
Abstract: Cloud computing is a very popular information technology, to obtain mutual trust and win-win cooperation between the users and the cloud service provider (CSP), we propose a game model-based trust prediction. Different participants have different motives and interests in the service game process. First, we use the Bayesian formula to predict the trust level of behavior attribute, further propose trust decision function and weight algorithm of trust attribute to ensure the accuracy by maximum dispersion principle. Second, we discuss the existence possibility of the game equilibrium and establishes a dynamic game model from the short-term benefit of the user. Third, from the long-term benefit of the CSP, we establish a tripartite game model that has multiple possible equilibria that can be converted into a mixed strategy under specific common conditions. Finally, we design simulation experiments to verify the regulation and several related factors have an important influence to improve trust and honesty and control the malicious behavior of participants; further, we compare and discuss the research results with other papers in the real data set scenario, and show the advantages and highlight value.